The Role of Peridomestic Animals in the Eco-Epidemiology of Anaplasma phagocytophilum - Lesiczka, Paulina Maria; Hrazdilová, Kristýna; Majerová, Karolina; Fonville, Manoj; Sprong, Hein; Hönig, Václav; Hofmannová, Lada; Papežík, Petr; Růžek, Daniel; Zurek, Ludek; Votýpka, Jan; Modrý, David (Microbial ecology, 2021)
Anaplasma phagocytophilum is an important tick-borne zoonotic agent of human granulocytic anaplasmosis (HGA). In Europe, the Ixodes ticks are the main vector responsible for A. phagocytophilum transmission. A wide range of wild animals is involved in the circulation of this pathogen in the environment. Changes in populations of vertebrates living in different ecosystems impact the ecology of ticks and the epidemiology of tick-borne diseases. In this study, we investigated four species, Western European hedgehog (Erinaceus europaeus), northern white-breasted hedgehog (Erinaceus roumanicus), Eurasian red squirrel (Sciurus vulgaris), and the common blackbird (Turdus merula), to describe their role in the circulation of A. phagocytophilum in urban and periurban ecosystems. Ten different tissues were collected from cadavers of the four species, and blood and ear/skin samples from live blackbirds and hedgehogs. Using qPCR, we detected a high rate of A. phagocytophilum: Western European hedgehogs (96.4%), northern white-breasted hedgehogs (92.9%), Eurasian red squirrels (60%), and common blackbirds (33.8%). In the groEL gene, we found nine genotypes belonging to three ecotypes; seven of the genotypes are associated with HGA symptoms. Our findings underline the role of peridomestic animals in the ecology of A. phagocytophilum and indicate that cadavers are an important source of material for monitoring zoonotic pathogens. Concerning the high prevalence rate, all investigated species play an important role in the circulation of A. phagocytophilum in municipal areas; however, hedgehogs present the greatest anaplasmosis risk for humans. Common blackbirds and squirrels carry different A. phagocytophilum variants some of which are responsible for HGA.
Keywords: ekosystém; Ixodes; Hedgehogs; Squirrel; HGA; zvířata; Humans; Anaplasma phagocytophilum; Hedgehog; nemoci přenášené klíšťaty; klíště; Tick-Borne Diseases; Urban wildlife; Blackbird; Ecosystem; Tick-borne diseases; lidé; ježkovití; Animals